55.6k views
1 vote
(1Q) Describe how to transform the graph of g(x) = lnx into the graph of f(x)= ln(x-4)+3?

(1Q) Describe how to transform the graph of g(x) = lnx into the graph of f(x)= ln-example-1

2 Answers

1 vote

Answer:

b

Explanation:

User Drashti Kheni
by
5.9k points
5 votes

Answer:

B

Explanation:

The correct answer is to go 4 units right (the direction is opposite to the sign) and 3 units up. The up and down direction is the same number as after the function.

Red: Parent Function y = ln(x)

Blue: 4 units right. 3 units up.

Answer: B

(1Q) Describe how to transform the graph of g(x) = lnx into the graph of f(x)= ln-example-1
User Divyang Shah
by
5.8k points